Security radar 2019: wake-up call for Europe - Krumm, Reinhard; Dienes, Alexandra; Weiß, Simon; Starystach, Sebastian; Schröder, Hans-Henning; Bär, Stefan (FES Regional Office for Cooperation and Peace in Europe, 2019)
﻿In the context of dramatic challenges for the European security order, the FES Regional Office for Cooperation and Peace in Europe (FES ROCPE) has completed a study on European security, based on a representative opinion poll on European security in seven countries: France, Germany, Latvia, Poland, Russia, Serbia, Ukraine. In addition to the general public, FES ROCPE also asked focus groups of consulting experts in each of the countries to add their perspective. This »Security Radar 2019« investigates the attitudes and values related to the current security and foreign policy situation in Europe. The goal is to produce an analysis for European decision makers and the general public, in order to promote the importance of a cooperative European Security Order and to provide fresh ideas for possible steps in that direction, without downplaying the enormous challenges.